The Role of a Notary Process of Making the Acquisition or Share Acquisition in the Order to Realize the Practice Healthy Business Competition - Henry Aspan; Anggy Auliawan; Ari Prabowo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Mergers, consolidations, and acquisitions can be a tool for business actors to get rid of their competitors. One of the merger guidelines that can be used to assess whether the consequences of a merger will affect business competition or not is the Merger Review Guidelines (MRG). In Article 29 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, it is expressly stated that business actors are obliged to report the occurrence of a merger no later than 30 days after the transaction. A notary is a public official who is authorized to make an authentic deed as long as the making of a certain authentic deed is not reserved for other public officials. From the point of view of laws and regulations, the position of a Notary in the acquisition process is very clear, especially in Government Regulation Number 27 of 1998 concerning Merger, Consolidation.